Blue Ocean Strategy in Managing Maritime Security - Sapto J. Poerwowidagdo (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2015)
The impact of the extension of the sea area of Indonesia, the biggest archipelagic state, is the bigger task of the Indonesian Navy and the other institutions and stake holder of the maritime security. The overlapping of the responsibility and authority in the maritime security tasks, pushes the Indonesian Navy in optimizing its main task. In the scope of the Maritime Domain Awareness, the Blue Ocean Strategy might be considered in managing an integrated maritime security by using Revolution in Navy Affairs in the Indonesian sea-power building